Microbial contamination of multiply used preservative-free artificial tears packed in reclosable containers. Issue 11 (9th September 2008) - Kim, M S; Choi, C Y; Kim, J M; Chung, H R; Woo, H Y
Abstract : Background/aims: To evaluate microbial contamination of multiply used preservative-free artificial tears packed in reclosable containers after daily use. Methods: Subjects were provided with preservative-free artificial tears (Groups 1 and 2) and artificial tears containing a preservative (Group 3). After administration three times or more per 10 h, bottles were collected, and any remaining fluid in the bottles was cultured. A risk factor analysis for microbial contamination was performed by the use of univariate and multivariate analysis. Results: A total of 242 eye-drop bottles were evaluated. Five (2.0%) of the 242 bottles had bacterial contamination. In group 1, four (3.9%) of 102 bottles were contaminated, and identified bacteria were all coagulase-negative Staphylococcus . In group 2, one (1.0%) of 105 bottles was contaminated, and it was a Gram-negative Acinetobacter species. No bottles from group 3 showed any contamination. Based on multivariate analysis, advanced age and fingertip touch were statistically significant risk factors for microbial contamination (p<0.05). Conclusion: Preservative-free artificial tears in reclosable containers are at risk of contamination in a daily and multiple use setting, especially in patients with a poor administering technique, which is associated with fingertip touch and advanced age.